ВИВЧЕННЯ МІКРОФЛОРИ НАСІННЯ СОЇ ЯК ОДНОГО З ЙМОВІРНИХ ФАКТОРІВ РОЗПОВСЮДЖЕННЯ BRADYRHIZOBIUM JAPONICUM - Крутило , Д.В. (Institute of Agrocultural Microbiology and Agro-industrial Manufacture of NAAS of Ukraine, 2008)
The results of studying of the soybean nodule bacteria presence in epiphytic and endophytic microflora of different grades of soybean seeds are presented. The soybean rhizobia was not revealed on the surface and in deep layers of soybean seeds. The soybean seed microbiota of investigated varieties is presented by several morphological types of bacteria and fungy. Their quantity depends on the period of seed storage.